Uma análise da canção enquanto ato litúrgico segundo Nicholas Wolterstorff: o caso das Novas Comunidades Católicas do Brasil. - GABRIEL SCATENA GUIZADO (2023)
This dissertation's theme is a popular song for liturgical purposes in the context of holding masses in the spirituality of new Catholic communities. The objective of this work is to present a model for the analysis of songs from the perspective of Nicholas Wolterstorff's theory of liturgical acts, as well as practical application through the analysis of songs taken from YouTube recordings referring to masses in the Canção Nova community. and Shalom. In chapter 1 we will present Wolterstorff's theory of liturgical acts and Austin's theory of speech acts, which will serve as a theoretical substrate for understanding the performative dimension of the liturgy proposed by the author. In chapter 2 we will present a systematic review of the regulations for staging a Catholic liturgy, using the Roman Missal of Paul VI as the main reference. Finally, chapter 3 will present the model for analyzing songs, as well as a new concept of liturgical song due to the articulation of different areas of knowledge such as: philosophy of language, theology and music and the analyzes obtained through practical application of the proposed tool. The results include the deepening of the liturgical musical issue post-Vatican Council II from a local perspective, the proposition of a tool that originated from the encounter between the various propositions of liturgical acts arising from the regulations for the performance of the mass and the theory of acts of speech and, finally, the analysis of the texts that discuss the different affective atmospheres that favor musical performance in the performative dimension of speech acts.